Establishment of a mathematical model for the analysis of anti-measles antibody reduction trend in children aged 1‒8 months - LI Shuhua; WANG Jingjing; ZHOU Jie; TANG Xihong; LING Hong (Shanghai yufang yixue, 2022)
ObjectiveTo determine the level of anti-measles antibody and its fluctuation trend in children under 8 months old， which may provide evidence for enhancing the measles immunization strategy.MethodsA cross-sectional study was conducted to collect the serum of the children aged 1‒8 months in a children’s medical center in Shanghai. Serum concentration of anti-measles IgG antibody was determined by enzyme-linked immunosorbent assay （ELISA）， and dynamics of IgG antibody level was compared.ResultsA total of 837 children aged 1‒8 months were tested for anti-measles antibody， and there was no statistical difference in the antibody level between boys and girls （P>0.05）. In the age of 1 month children， the average geometric antibody concentration （GMC） was 529.66 IU‧L-1， and the antibody positive rate and protection rate were 86.07% and 29.51% respectively. After the age of 3 months， the antibody level dropped sharply in the age of 8 months children， the GMC decreased to 44.46 IU‧L-1. The positive rate was 12.00%， and the protection rate was 1.00%. The mathematical model of GMC reduction trend in children aged 1‒8 months was Ŷ=-0.144 8X+2.640（R2=0.911 3， P<0.001）.ConclusionThe low level of mother-transmitted protective antibody and its downward trend with age are the important factors leading to the incidence of measles in children aged 1‒8 months. It is suggested that intensive immunization should be carried out for women of childbearing age to improve the level of mother-transmitted antibodies in her baby.